2015
DOI: 10.1099/mic.0.000127
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining of fungal lipid-degrading enzymes for industrial applications

Abstract: Lipases are interesting enzymes, which contribute important roles in maintaining lipid homeostasis and cellular metabolisms. Using available genome data, seven lipase families of oleaginous and non-oleaginous yeast and fungi were categorized based on the similarity of their amino acid sequences and conserved structural domains. Of them, triacylglycerol lipase (patatin-domaincontaining protein) and steryl ester hydrolase (abhydro_lipase-domain-containing protein) families were ubiquitous enzymes found in all sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Isolation and screening of microorganisms have been applied as a strategy to obtain strains able to produce industrially-relevant enzymes. Considering the increased number of available genomes, new rational approaches, such as genome mining, provide an attractive alternative to labor-intense screenings [ 1 , 2 ]. This is also an interesting alternative to target the prospection of enzymes in fungi deposited in culture collections.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation and screening of microorganisms have been applied as a strategy to obtain strains able to produce industrially-relevant enzymes. Considering the increased number of available genomes, new rational approaches, such as genome mining, provide an attractive alternative to labor-intense screenings [ 1 , 2 ]. This is also an interesting alternative to target the prospection of enzymes in fungi deposited in culture collections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the common consensus signature motifs (GxSxG and GDSL), several studies have reported a set of specific consensus motifs using alignment of similar homologous sequences. For example, the GxxR motif (GxxR), the GTK motif and the unidentified motif (SLLTxxTPH) are though to play a role in substrate selectivity in the steryl ester hydrolase family, the triacylglycerol lipase family and the acylglycerol lipase family, respectively (Vorapreeda et al 2015). These motifs provide specific biological benefits relevant to the function of the c Fig.…”
Section: Homology-based Mining Of Lipase Genesmentioning
confidence: 99%
“…Therefore, integrative analysis of amino acid sequence similarity with information relevant to conserved structural domains was introduced to classify lipid-degrading enzymes in eukaryotic microorganisms. Based on this strategy, the fungal lipid-degrading enzymes were recently classified into seven families, which have led to improved functional prediction and categorization of fungal enzymes (Vorapreeda et al 2015). The functional conserved domains of the interesting proteins may be identified simply by comparing the amino acid sequences against conserved protein family databases, such as Pfam (Finn et al 2016) and CDD (Marchler-Bauer et al 2015).…”
Section: Homology-based Mining Of Lipase Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Asia, in particular China, has focused on economically important fungi in many genome projects. The landscape of Asian genomic and functional genomic projects have concentrated on areas, such as plant and human pathogenic fungi [21], fungal-host interactions [77,78], fungi as biocontrol agents [79], fungi as food [80] and medicinal fungi [20,81]. Asian large scale sequencing bodies, such as Beijing Genomics Institute (China), Macrogen (Korea), Chun Lab (Korea), Softbank (Japan), Temasek (Singapore), Prenetics (Hong Kong), Xcode (India) and Genomico (Iran), have also been collaborating with large scale fungal genomic projects.…”
Section: Genomicsmentioning
confidence: 99%